2013
DOI: 10.1159/000355826
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma: Relationship to Antioxidant Esterases

Abstract: Objective: To investigate the status of the oxidant/antioxidant balance in patients with multiple myeloma compared to healthy controls. Materials and Methods: This study was conducted on 40 multiple myeloma patients and 40 healthy controls of matched age and sex. Serum total thiol, oxidative stress index (OSI), total oxidant status (TOS), and total antioxidant status (TAS) were measured using colourimetric methods; paraoxonase-1 and arylesterase enzyme activities were also quantified. Results: Serum paraoxonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Moreover, 8-isoprostane levels have not been studied in MM. 25 In other studies on the reduction of PON1 activity in tumors, researchers have investigated the activity of this enzyme in patients with esophageal squamous, 26 pancreatic, 27 and gastric cancer 9 and found low HDL and PON1 levels. Elkiran et al found even lower levels of PON1 activity in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 8-isoprostane levels have not been studied in MM. 25 In other studies on the reduction of PON1 activity in tumors, researchers have investigated the activity of this enzyme in patients with esophageal squamous, 26 pancreatic, 27 and gastric cancer 9 and found low HDL and PON1 levels. Elkiran et al found even lower levels of PON1 activity in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated serum levels of antioxidants such as superoxide dismutase (SOD1), glutathione peroxidase, catalase and vitamins C and E were lower, whereas serum levels of oxidative stress markers (including malondialdehyd and advanced oxidation protein products) were higher in multiple myeloma patients compared to healthy individuals [38-42]. Accordingly, activities of antioxidants preventing lipid peroxidation such as paraoxonase (PON1) and arylesterase (ARE) were lower in multiple myeloma patient sera [43,44]. Levels of 8-isoprostane, a product of fatty acid peroxidation, were on the contrary higher in multiple myeloma patients [43].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Levels of 8-isoprostane, a product of fatty acid peroxidation, were on the contrary higher in multiple myeloma patients [43]. Moreover, decreased activities of ARE and PON1 were proposed as poor prognosis markers for a subgroup of multiple myeloma patients [44]. Additionally, serum levels of scavenger receptor class A member 3 (SCARA3), a protein protecting cells from oxidative stress, inversely correlated with myeloma progression in patients [45].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In all age subgroups of women, HDLC levels were significantly higher compared to men in our study. On the other hand, it has been recently ac knowledged that HDL functionality is more critical than its concentration [19,42,43]. PON1 and ARE, which are important indicators of HDL function, are multifunctional enzymes that have antioxidant, antiatherogenic, lactonase and homocysteinethio lactonase activities [44,45].…”
Section: Parametersmentioning
confidence: 99%